2021
DOI: 10.26650/eor.2022807392
|View full text |Cite
|
Sign up to set email alerts
|

Changes in airway patency and sleep-breathing in healthy skeletal Class II children undergoing functional Activator therapy

Abstract: How to cite: Medina CC, Ueda H, Iwai K, Kunimatsu R, Tanimoto K. Changes in airway patency and sleep-breathing in healthy skeletal Class II children undergoing functional activator therapy. Eur Oral Res 2022;56(1):XX-XX.This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Six studies [ 15 , 16 , 17 , 18 , 19 , 20 ] containing data on cephalometric and polysomnographic outcomes after dental appliance application in OSA patients were included ( Table 1 ). The initial search found 619 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies [ 15 , 16 , 17 , 18 , 19 , 20 ] containing data on cephalometric and polysomnographic outcomes after dental appliance application in OSA patients were included ( Table 1 ). The initial search found 619 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mean age and BMI are depicted in Table 1 . Three studies [ 15 , 17 , 19 ] describing 102 patients reported mean age and BMI in their respective cohorts. No significant difference in age was found between the two groups (mean difference: 0.52 years, 95% CI: [0.41, 1.46], p = 0.27, Chi 2 = 6.34, I 2 = 68%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the orthodontist after surgical removal, with the rapid expansion of the maxilla and even with intraoral appliances of mandibular advancement (11)(12)(13)(14), depending on the skeletal deformity, allows an improvement in the respiratory picture, apparently reducing the AHI of cases of persistent OSAHS (2). However, studies of orthopedic/orthodontic therapy in the improvement of OSAHS Development and its applications in scientific knowledge…”
Section: Dental Approachmentioning
confidence: 99%